A bio-orthogonal linear ubiquitin probe identifies STAT3 as a direct substrate of OTULIN in glioblastoma. Issue 3 (20th January 2023) - Du, Xianli; Pang, Jing; Gu, Bin; Si, Tian; Chang, Yan; Li, Tianqi; Wu, Min; Wang, Zicheng; Wang, Yuxia; Feng, Jiannan; Wu, Ning; Man, Jianghong; et al.
Abstract: While linear ubiquitin plays critical roles in multiple cell signaling pathways, few substrates have been identified. Global profiling of linear ubiquitin substrates represents a significant challenge because of the low endogenous level of linear ubiquitination and the background interference arising from highly abundant ubiquitin linkages (e.g. K48- and K63-) and from the non-specific attachment of interfering proteins to the linear polyubiquitin chain. We developed a bio-orthogonal linear ubiquitin probe by site-specific encoding of a norbornene amino acid on ubiquitin (NAEK-Ub). This probe facilitates covalent labeling of linear ubiquitin substrates in live cells and enables selective enrichment and identification of linear ubiquitin-modified proteins. Given the fact that the frequent overexpression of the linear linkage-specific deubiquitinase OTULIN correlates with poor prognosis in glioblastoma, we demonstrated the feasibility of the NAEK-Ub strategy by identifying and validating substrates of linear ubiquitination in patient-derived glioblastoma stem-like cells (GSCs). We identified STAT3 as a bona fide substrate of linear ubiquitin, and showed that linear ubiquitination negatively regulates STAT3 activity by recruitment of the phosphatase TC-PTP to STAT3. Furthermore, we demonstrated that preferential expression of OTULIN in GSCs restricts linear ubiquitination on STAT3 and drives persistent STAT3 signaling, and thereby maintains the stemness and self-renewal of GSCs. Graphical Abstract: